Problem rozwodu i powtórnego małżeństwa w pierwotnym Kościele do Soboru Nicejskiego włącznie - Góralski, Wojciech (Ius Matrimoniale, 2016)
The inseparability of marriage, which originates from God’s law, underlies canonical marriage system and is a significant novum in relation to the institution of marriage functioning in ancient Jewish and Greco-Roman traditions, has been problematic since the beginning. This results from the fact that that all ancient legislation of the East: Egypt, Greece and Rome allowed to divorce and remarry. Breaking the matrimonial bond was a common practice and was not questioned by the public. Therefore, conversion of traditional marriage practices used in the above mentioned legislations was a serious challenge for Christians and very often turned to be difficult. All the more so because – in the opinion of Jean Gaudemet – the content related to indissolubilitas matrimonii found in the Gospels was not clear. Despite that fact, the message concerning the inseparability of marriage, included both in the Gospels and in the Epistles of Saint Paul, motivated the followers of the Church to raise awareness in this important matter. The issue of inseparability of marriage was expressed in the teachings of religious writers and Patristic theologians of the first centuries, both Greek and Latin. Acknowledging remarriage (excluding widows and widowers) as forbidden as long as the other spouse is alive, was especially typical. Basing on Biblical texts, religious writers and the fathers of the Church definitely disavowed remarriage by those who were already married. It is very significant that when it comes to Matthew’s clause (5, 32 and 19,9 ) it was commonly believed that a betrayed husband did not have a right to remarry. Synods of IV century were of high importance in this matter as well. The most important document of the early-Christian period, related to the issue of divorce and remarriage is canon 8 of the Council of Nicaea, established in response to the errors of Novatian’s sect, which rejected any kind of remarriage. Among conditions that had to be met to be accepted into Church was the condition to remain in the community with those who “married twice”. Because of the above mentioned conciliar Canon did not specify which bigamist it referred to (whether those who remarried after becoming a widow/widower or those who got divorced), there were questions concerning interpretation. Whereas some authors (especially Giovanni Cereti) assume that both widowers and divorced people who remarried and were accepted in the Church should be able to belong to it, the majority of the them (especially Henri Crouzel) believed that when establishing canon eight, the fathers of the Council of Nicaea meant that only widows and widowers can remarry. Later testimonies of Latin fathers of the Church of IV and the beginning of V century, who faced the issue of divorce and remarriage, constitute a significant argument supporting this view.